2004
DOI: 10.1021/jp036911n
|View full text |Cite
|
Sign up to set email alerts
|

The Multiplicity, Strength, and Nature of the Interaction of Nucleobases with Alkaline and Alkaline Earth Metal Cations:  A Density Functional Theory Investigation

Abstract: Density functional theory (DFT) calculations were performed at the B3LYP/6-311++G(d,p) level to systematically explore the geometrical multiplicity and binding strength for the complexes formed by alkaline and alkaline earth metal cations, viz. Li + , Na + , K + , Be 2+ , Mg 2+ , and Ca 2+ (M n+ , hereinafter), with nucleobases, namely, adenine, cytosine, guanine, thymine, and uracil. Morokuma decomposition and orbital analysis were used to analyze the binding components. A total of 150 initial structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 30 publications
5
92
4
1
Order By: Relevance
“…Conventional p complexes, that is, forms c and d are found [10] to be local minima on the potential energy surface. These conventional p complexes are also formed [43] on the interaction with alkali and alkaline earth metal cations, although they are less stable than complexes in which the cation interacts with the heteroatom. Similarly, for Cu + these structures were also found to be much higher in energy (about 176 kJ mol À1 ) than the previously mentioned structures a and b, but they play an important role in the gasphase reactivity of [CuA C H T U N G T R E N N U N G (uracilÀH)] + complexes.…”
Section: H T U N G T R E N N U N G (Uracilàh)]mentioning
confidence: 95%
“…Conventional p complexes, that is, forms c and d are found [10] to be local minima on the potential energy surface. These conventional p complexes are also formed [43] on the interaction with alkali and alkaline earth metal cations, although they are less stable than complexes in which the cation interacts with the heteroatom. Similarly, for Cu + these structures were also found to be much higher in energy (about 176 kJ mol À1 ) than the previously mentioned structures a and b, but they play an important role in the gasphase reactivity of [CuA C H T U N G T R E N N U N G (uracilÀH)] + complexes.…”
Section: H T U N G T R E N N U N G (Uracilàh)]mentioning
confidence: 95%
“…All results from these studies not only accorded with the reported data in the literature, but characterized the binding nature of cation-π interactions. For example, the calculated results showed that the binding of alkali and alkaline-earth ions with nucleobases could be divided into two different types: one is cation-heteroatom binding similar to hydrogen bonds; another is cation-π interactions [38] . Cation-π binding evidently distorts the planar ring structure of nucleobases because the binding strength is very strong (up to several hundred kcal·mol −1 ), suggesting cation-π interactions are of sufficient strength to play important roles in maintaining the structure and function of nucleic acids.…”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 99%
“…Different cation-π systems possess different proportions of binding components. Since 1997, Zhu and Jiang et al [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have performed systematic investigations on cation-π interactions by quantum chemical methods. The investigated cations included alkali metal, alkaline-earth metal, NH 4 + , CH 3 NH 3 + , and tetramethylammonium (TMA); the aromatic systems included benzene, substituted benzene, 5-membered and 6-membered aromatic heterocyclic rings, 8-membered aromatic rings, all kinds of aromatic residues and nucleobases.…”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 99%
“…We studied mono-and bi-coordination modes and we considered that deprotonation could occur on several sites: nitrogens, C(5), and oxygens or sulfurs for tautomeric forms. We decided not to investigate in detail -interactions because of the resulting distortion of the ring from planarity, which destroys the resonance delocalization and leads to high-energy species [33,41]. Relevant bond lengths of the most stables structures obtained are given in Figure 3.…”
Section: Structures and Relative Stabilities Of [Pb(thiouracil) ϫ H]mentioning
confidence: 99%